Factors Related to Personal Hygiene of Traditional Jamu Handler in Bantul District, Indonesia - Suryani, Dyah; Indriani, Atika Rahma; Suyitno, Suyitno (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: Foodborne disease is the contamination of pathogenic bacteria that multiply in drinks. Traditional jamu handlers, people who process conventional jamu, need to implement and understand the importance of personal hygiene to avoid bacterial contamination. Aims: This study aimed to determine the relationship between knowledge, attitude, sanitation facilities and infrastructure, participation in counseling, and level of education with personal hygiene in traditional jamu handlers in Kiringan Village, Bantul District, Yogyakarta Province, Indonesia. Methods: This study used a quantitative approach with a cross-sectional design, involving 73 traditional jamu handlers who were selected by simple random sampling from a population of 90 handlers. The dependent variable was the personal hygiene of jamu handlers, measured using an observation checklist and categorized as